PENGARUH LAMA RENDAMAN KOTORAN SAPI TERHADAP CAMPURAN ASPAL BETON MENGGUNAKAN ASPAL PEN.60/70 YANG DISUBSTITUSI LIMBAH POLYETHYLENE TEREPHTHALATE (PET) - Liza Afra; Sofyan M. Saleh; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2018)
Cow Feces is alleged impact on damage to highways that can weaken the ability of the asphalt viscosity and cause small holes in the asphalt. This study, the substitution polymer used is a waste material Polyethylene Terephthalate (PET) on the AC-WC which were soaked with cow feces. This study aims to determine the effect of immersion duration of cow feces on the durability of concrete asphalt mixture using asphalt pen. 60/70 with substitution grated PET polymer waste 5%, 7%, 9% with asphalt pen 60/70 weight ratio, as well as determine the effect of plain water immersion and cow feces with a variation of 30 minutes, 24 hours, and 48 hours on the stability of asphalt modification with PET. The results, value asphalt optimum 5.52%, the best stability values without substitution with palin water immersion cow feces is 1136,49 kg, the best stability for PET on a percentage of 9%, is 2092,01 kg. The value of durability without substitution with plain water immersion is 92,64% by soaking into coe feces, the value of the durability of the PET percentage variation is 99,72%, and has met the prescribed Bina Marga specifications 2014 which ≥ 90%. The best percentage of PET polymer addition in this study was 9% because it has the best stability and durability value